Silica accumulation in grasses in response to a large scale herbivore exclosure experiment - Herranz Jusdado, Juan German (Universitetet i Tromsø, 2011)
Silica defenses in grasses have been recently proposed to be important for plant-herbivore interactions. High silica levels in grasses have been found to have a negative impact on herbivores performance and act as an herbivory deterrent. Moreover, accumulation of silica has been proposed to be inducible, i.e. highly grazed grasses accumulate silica in their leaves. In order to assess whether silica induction is an important mechanism of plant-herbivore interactions also in sub-arctic ecosystems, we conducted a large-scale herbivore exclosure experiment in northern Norway. We measured silica concentrations in leaves of five common grass species. Two species showed differences in silica concentrations when herbivory was excluded and one species showed variation in the levels of silica between areas of different grazing pressure, otherwise, we found no clear results supporting silica accumulation in grasses as an important response to herbivory in sub-arctic areas. Silica uptake in grasses is a complex process, regulated by several factors, where herbivory is one of them, but other abiotic factors (i.e. temperature, pH of the soil, etc.) may mask the effect of herbivory in gasses silica accumulation. A better understanding of the biotic and abiotic factors that affects silica induction is necessary to interpret correctly the role of silica in plant-herbivore interactions.